Synthesis of Ionic Salt for Calcite and Barite Solid Scale Dissolution - M. H., Sulaiman; Fatmawati, Adam; Zulkefli, Yaacob; Zulhaizan, Mohd Noor (IOP Publishing, 2020)
The most common well intervention work to solve solid scale problem in oil production is a treatment to remove or inhibit the solid scale. Calcite (CaCO3) and barite (BaSO4) are two of the most common solid scale found in the oil well tubular and piping. Often, acid treatment such as hydrochloric acid is used to dissolve the solid scale. However, acid is highly corrosive and harmful to handle in the challenging environment of oilfield operation. A new generation of less corrosive solid scale dissolver includes functional group such as a carboxylic group due to its ability to chelate metals ions. This study utilised economical and non-toxic materials, monosodium glutamate (MSG), as the starting materials to synthesis solid scale dissolver with the carboxylic group as the main functional group presence. The double step acidification of MSG produces glutamic acid hydrochloride (GluCl). It is solid at room temperature and soluble in water makes it safer to transport and handle in the challenging environment of oilfield operation. Dissolution test shows that GluCl can dissolve more than 3000 ppm of calcium at a concentration of just 20g/L.